THE ISSUE OF HINDUISM CONFESSION AND INDIAN DIASPORA IN BUKHARA EMIRATE (American Journal of Research in Humanities and Social Sciences, 2022)
An insight provided at the article reviews of the history of the Hindu denomination in Central Asia in the late 19th and early 20th centuries, especially in the Bukhara Emirate. The relations of the Indian diaspora and confession with other religions during the tsarist period of Bukhara and their activities here are also studied on the basis of historical sources and the archival documents.